Diversity of fruit fly species (Diptera: Tephritidae) associated with citrus crops (Rutaceae) in southern Benin in 2008-2009 - Vayssières, Jean-François; Adandonon, A.; Sinzogan, A.A.C.; Korie, S. (2010)
Fruit flies are pests of economic importance in many fruit crops. Little was known about Tephritid diversity in citrus orchards in southern Benin prior to this study. Traps baited with parapheromones were set in citrus orchards from August 2008 to August 2009 in the Atlantique, Ouémé and Zou departments to identify fruit fly species and monitor the fluctuation of their populations. Citrus fruits were also sampled during the citrus season (from August 2008 through August 2009) at two-week intervals and assessed in the laboratory for fruit fly damage. Other cultivated and wild fruits near the citrus orchards were also collected. The fruit fly detection trapping showed that Bactrocerainvadens Drew Tsuruta & White followed by Dacus bivittatus (Bigot), was the most predominant species recorded in Citrus orchards.Bactrocera cucurbitae (Coquillett) was also recorded along with six species of Ceratitis. From all fruits sampled, the emerged fruit fly species were primarily B. invadens (98.3%), followed by B. cucurbitae, Ceratitis fasciventris (Bezzi), Ceratitis ditissima (Munro), Ceratitis anonae Grahamand Dacus punctatifrons Karsch. The infestation rate was highest on Citrus reticulata Blanco (22%), followed by C. tangelo Macfad (18.7–19.7%) and Citrus sinensis Osbeck (5.3–8.74%). These results are significant for the decision-making process for effective monitoring and management of B. invadens in citrus orchards in southern Benin.